2023
DOI: 10.1186/s12939-023-02014-1
|View full text |Cite
|
Sign up to set email alerts
|

Racism against racialized migrants in healthcare in Europe: a scoping review

Mia Pattillo,
Sigsten Stieglitz,
Konstantinos Angoumis
et al.

Abstract: Background Racism is frequently mentioned as a social determinant of migrants’ health and a barrier to health services. However, in the European context, racism and its impact on racialized migrants’ access to healthcare is remarkably under-researched. This scoping review makes a first step toward filling this void by mapping the existing literature on racial and ethnic discrimination against racialized migrants in healthcare in Europe, identifying evidence gaps, and offering recommendations fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
(179 reference statements)
1
7
0
Order By: Relevance
“…Nong et al [ 22 ] found that such experiences also are associated with lower trust in the health care provider and a reduced willingness to share information with the provider, possibly resulting in lower quality of medical decision-making and care. These findings, together with the results presented here underline that discrimination is an important aspect of inequalities in health and health care [ 5 7 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 76%
“…Nong et al [ 22 ] found that such experiences also are associated with lower trust in the health care provider and a reduced willingness to share information with the provider, possibly resulting in lower quality of medical decision-making and care. These findings, together with the results presented here underline that discrimination is an important aspect of inequalities in health and health care [ 5 7 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 76%
“…Evidence suggests that ethno-racial minorities are more likely to receive welfare sanctions in the US and to be denied social insurance benefits, stopped or subject to discriminatory profiling by the police in Sweden [ 12 , 50 ]. Experiences of discrimination within healthcare have also been reported in various settings [ 21 , 31 , 32 ]. Such discrimination is worrisome as it can contribute to a distrust in public institutions and reluctance to seek available services and support, and result in unequal opportunities in accessing these services between migrant and non-migrant groups [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between experiences of ethno-racial discrimination and access to healthcare has also been highlighted in several studies. Perceived ethno-racial discrimination has been identified as a barrier to care for migrants that reinforce inequities in healthcare access and quality for racialized migrants in several studies in Sweden and elsewhere [ 21 , 31 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Racism towards racialized immigrants in accessing and receiving healthcare has been observed at interpersonal and structural levels and constitutes a barrier to equity in healthcare. Racism has been associated with delay in seeking healthcare, lack of trust, feelings of being ignored and with differential medical treatment [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%